Effect of OutsourcingHuman Resources and Organizational Performance in Public Universities in Kenya - Matolo, Rose Syombua; Iravo, Mike (International Journal of Humanities and Social Science, 2018)
The paper outlines the relationship between outsourcing Human Resources and the performance of the organizational performance. It focuses on the public universities in Kenya.According to research done, Human Resource Outsourcing improves efficiency (Sang, 2010). The independent variables are reduction of cost, access to technology, allowing HR Personnel to focus on the strategic functions and focusing on the core competences. The research concludes by indicating that there is an overall benefit in terms of organizational performance when organizations outsource their Human Resources thus creating competitive advantage.
Keywords: Outsourcing; Human Resource Management; Performance; Public Universities in Kenya.